Total Tear Acl and Partial Tear Pcl in Football Athletes at Semarang City Hospital - Supardi, Supardi (Research of Service Administration Health and Sains Healthys, 2020)
This study aims to determine the role of physiotherapy on the handling of post- operative ligament and determine through TENS, CRYOTHERAPI, SWT physiotherapy and exercise therapy (TL) in overcoming problems in ACL injuries. To find out from an injury in need assessment of the history of the disease, either history or examination. Well directed anamnesis thorough examination can be obtained a proper diagnosis. Examination was conducted in order to determine the existing problems in athletes post ACL surgery, prepare therapeutic purposes and determine appropriate modalities. Screening measures include anamnesis, physical examination of a specific examination is the subjective examination and objective examination. Furthermore, the implementation of physiotherapy by means of TENS, CRYOTHERAPI, SWT, which is a way of useful electrical energy to stimulate the nervous system through the skin surface and proven effective for reducing various types of pain. The conclusion of this study was: 1) Provision of TENS in the case of post ruptured anterior ligament carciatum aims to reduce pain through the mechanism of segmental and 2) a reduction in pain after treatment action for six times. Exercise therapy can provide pain reduction effect, both directly and break the cycle of pain spasm→ pain. Light and movement will slowly stimulate proprioceptor which is the activation of large diameter afferent fibers. Granting Therapeutic Exercise in the case of post reconstruction craciatum anterior ligament which is to improve balance and improve muscle strength.